2005
DOI: 10.1097/01.brs.0000188400.11490.5f
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity and Specificity of Electrodiagnostic Testing for the Clinical Syndrome of Lumbar Spinal Stenosis

Abstract: This first masked study in the 60-year history of needle electromyography also introduces anatomically validated needle placement, quantified and reproducible examination of the paraspinal muscles, and dual control populations to EDX research in spinal disorders. EDX has statistically significant, clinically meaningful specificity for spinal stenosis and detects neuromuscular diseases that may masquerade as stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 36 publications
3
71
0
5
Order By: Relevance
“…More advanced disease may demonstrate significantly decreased nerve conduction, with axonal loss and evidence of demyelination in a multi-radicular pattern [16][17][18][19] . treatment Before any treatment proposal, it is important to know the natural history of the disease.…”
Section: Radiological Findingsmentioning
confidence: 99%
“…More advanced disease may demonstrate significantly decreased nerve conduction, with axonal loss and evidence of demyelination in a multi-radicular pattern [16][17][18][19] . treatment Before any treatment proposal, it is important to know the natural history of the disease.…”
Section: Radiological Findingsmentioning
confidence: 99%
“…We are aware that EMG studies including paraspinal recordings were shown to be sensitive in lumbar spinal canal stenosis [23]. Such EMG recordings become positive as soon as an axonal nerve root damage is established.…”
Section: Discussionmentioning
confidence: 98%
“…These processes represent common flaws during the differential diagnosis of atypical claudication, because imaging studies are not specific for LSS [19]. Although electrodiagnostic testing is highly specific for the diagnosis of LSS [20], its clinical utilization is limited due to the high cost and invasiveness.…”
Section: Discussionmentioning
confidence: 99%